Effects of Exercise Frequency and Intensity on Reducing Depressive Symptoms in Older Adults With Insomnia: A Pilot Randomized Controlled Trial - Chin, Edwin C.; Yu, Angus P.; Leung, Chit K.; Bernal, Joshua D.; Au, Whitney W.; Fong, Daniel Y.; Cheng, Calvin P.; Siu, Parco M. (Frontiers in Physiology, 2022)
Background The effects of exercise frequency and intensity on alleviating depressive symptoms in older adults with insomnia are unclear. Purpose The purpose of this study was to investigate the influence of different exercise frequencies and intensities on prescribed aerobic-type physical activity (i.e., 75 min of vigorous-intensity exercise or 150 min of moderate-intensity exercise weekly) for reducing depressive symptoms in older adults living with insomnia, as recommended by the WHO. Design This study is a randomized, controlled, assessor-blinded trial. Setting This study is conducted at a single research site in Hong Kong. Participants This study includes older adults aged 50 years or above with depressive symptoms and insomnia. Intervention Participants were randomly assigned in a 1:1:1:1:1 ratio to the following groups: attention control (CON), moderate walking once weekly (MOD × 1/week), moderate walking thrice weekly (MOD × 3/week), vigorous walking once weekly (VIG × 1/week), and vigorous walking thrice weekly (VIG × 3/week). The total weekly exercise volumes among the walking groups were matched to the minimum recommended physical activity volume. Measurements Depression, anxiety, self-perceived sleep quality, insomnia severity, actigraphy-assessed 7-day sleep data, 7-day sleep diary, cardiorespiratory fitness, adherence, and habitual physical activity were examined at baseline and after 12 weeks of intervention. Results Both MOD × 3/week and VIG × 3/week groups demonstrated reduced depression (Hospital Anxiety and Depression Scale [HADS] – Depression: MOD × 3/wk: −68.6%; VIG × 3/week: −67.4%) and anxiety levels (HADS – Anxiety: MOD × 3/week: −54.3%; VIG × 3/week: −59.8%) compared with CON (both p < 0.01). Self-perceived sleep quality was improved in MOD × 3/week (−31.4% of the Pittsburgh Sleep Quality Index [PSQI]), VIG × 1/week (−34.1% of PSQI), and VIG × 3/week (−38.3% of PSQI), but not in MOD × 1/week, when compared with CON (p < 0.05). No serious adverse events were observed in this study. Conclusion The effects of walking training on reducing depressive symptoms appeared to be dependent on exercise frequency. Our findings suggest that three sessions of walking per week at either moderate or vigorous-intensity effectively alleviate depressive symptoms in older adults with insomnia. Additional research is needed to further verify the effects of exercise frequency on depression. Clinical Trial Registration [ClinicalTrials.gov], identifier [NCT04354922].